ETNOGRAFI VIRTUAL PRAKTIK DIGITAL VIGILANTISM NETIZEN DI THREADS PADA KASUS TUMBLER TUKU - Dwi Ari Sandy, Seviola; Mustika Chairil, Augustin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the Tuku Tumbler case, which was widely discussed on various social media. The netizens' responses, which tended to be against it, were prominent and even resulted in real consequences, such as the loss of a job for one of the parties involved. This case then received widespread attention from online media and was linked to the phenomenon of digital vigilantism. This study aims to analyze how digital vigilantism practices were carried out by netizens on Threads in the Tuku Tumbler case. The method used was a descriptive qualitative approach with virtual ethnography according to Christine Hine, and used Trottier's concept of digital vigilantism and Henry Jenkins' theory of participatory culture as the basis for analysis. Data were collected through observation and literature review. The results of the study indicate that digital vigilantism practices carried out by netizens include naming, shaming, online harassment, doxing, reporting to the workplace to get the target fired, and proposing a boycott of PT KAI to stop using train services. The targets were not only the main perpetrator, but also extended to other parties such as husbands and KAI staff. This practice manifests itself in various forms of digital expression, both verbal and nonverbal, as a form of collaboration among netizens to create a deterrent effect and exert social pressure, as a form of social sanction, as well as an effort to uphold justice and damage the target's reputation. Repost and share features also accelerate the spread of information. Netizen participation in this practice has been shown to have significant social and economic impacts on the targeted parties.